Experiences of wellbeing and resilience among refugee mothers and families in Calgary during the COVID-19 pandemic, and the role of participation in HIPPY, a home visiting program - Chloe Zivot; Cate Dewey; Meghan Brockington; Chioma Nwebube; Ghaid Asfour; Natasha Vattikonda; Debbie Bell; Sharada Srinivasan; Matthew Little (AIMS Press, 2022)
In order to provide meaningful and effective support to refugees in Canada during the COVID-19 pandemic, as well as during post-pandemic recovery efforts, it is critical to explore the experiences of refugee mothers and families during the pandemic, and to identify sources of resilience that can be leveraged to promote individual and household wellbeing. From November 2020 to June 2021, we conducted in-depth interviews with mothers from refugee backgrounds (n = 28) who resettled in Calgary, Alberta and are currently participating in the Multicultural Home Instruction for Parents of Preschool Youngsters (HIPPY) program. Interviews were conducted virtually using Microsoft Teams; we sought to better understand the pathways and barriers to wellbeing experienced by refugee mothers during the pandemic. The results indicate that the refugee mothers and families in our study experienced widespread disruptions to education and employment and increased motherhood burden, contributing to diminished wellbeing. Mental health was further impacted by heightened levels of worry, stress and social isolation, as well as intense fear pertaining to the spread of SARS-CoV-2. Some mothers reported experiencing barriers to accessing healthcare services and reliable health information during the pandemic. In the face of these challenges, the mothers demonstrated great resilience and identified tangible individual, household and extra-household factors and resources that supported them in coping with the impact of the COVID-19 pandemic. Additionally, our findings suggest that participation in HIPPY played a significant role in fostering the resilience of the participating mothers and families during the pandemic, speaking to the potential of home visiting intervention models in mitigating household hardship during current and future public health crises.